SEASONAL VARIATION AND DIVERSITY OF BACTERIA OF THE VIBRIO AND SALMONELLA GENERA ISOLATED IN A FEW UNDERGROUND WATER POINTS DEVELOPED IN THE COMMUNE OF NTUI (MBAM-ET-KIM DEPARTMENT, CENTER-CAMEROON) - Baleng, Samuel Davy; Noah Ewoti, Olive Vivien; Kenne, Berenger Patrick Tchinda; Metsopkeng, Claire Stéphane; Djiala, Morelle Raisa Tagne; Ladibé, Pélagie; Nola, Moses (International Journal of Research -GRANTHAALAYAH, 2022)
A study aimed at evaluating the seasonal variation of Vibrio and Salmonella in the developed groundwater used for drinking water in the commune of Ntui, Center Region of Cameroon was conducted from January to July 2021. The microorganisms sought were Aerobic Heterotrophic Mesophilic Bacteria (BHAM), bacteria of the Vibrio and Salmonella genera. These bacteria were isolated from ten (10) groundwater points by the surface spreading technique on ordinary agar for BHAMs and that of filter membranes on Thiosulfate Citrate Bile Sucrose (TCBS) and Salmonella-Shigella (SS) media. for Vibrio and Salmonella respectively. Some abiotic parameters such as temperature, pH, among others were evaluated using the usual techniques. The results show that some physico-chemical parameters such as temperature vary relatively between the sampling points. There is a slightly acidic average pH of 6.86 ± 0.57 U.C which is therefore a function of the lateritic soils crossed by the waters. Bacteriological analyzes revealed that these waters have a high and varied bacterial load. Densities of pathogenic bacteria reached an average of 80 CFU/100mL for Vibrio and 7.4.102 CFU/100mL for Salmonella. The most represented bacterial species identified were Vibrio cholerae and Salmonella enterica. These germs can be the cause of cholera and typhoid epidemics in this municipality. Significant correlations (P<0.05) between bacterial abundances and pH were observed. The degradation of the quality of these waters is caused by their proximity to sources of pollution. According to European Union standards, these waters are not recommended for human consumption without any prior treatment.